Cerebral Responses to Stationary Emotional Stimuli Measured by fMRI in Women with Persistent Postural-Perceptual Dizziness - von Söhsten Lins,Eliane Maria Dias (2021)
Abstract Introduction Persistent postural-perceptual dizziness (PPPD) is a functional vestibular disorder characterized by chronic dizziness, unsteadiness, and hypersensitivity to motion. Preexisting anxiety disorders and neurotic personality traits confer vulnerability to PPPD. High anxiety during acute vertigo or dizziness incites it. A functional magnetic resonance imaging (fMRI) study of chronic subjective dizziness found unexpectedly hypoactive responses to vestibular stimulation in cortical regions that integrate threat assessment and spatial perception. Objective This fMRI study used non-moving, but emotionally charged visual stimuli to investigate the brain's activity of PPPD patients and control subjects. Methods The participants included 16 women with PPPD and 16 age-matched women who recovered completely from acute episodes of vertigo or dizziness capable of triggering PPPD. Brain responses to positive, neutral, and negative figures from the International Affective Picture System were measured with fMRI and compared between the groups. Dizziness handicap, anxiety, and depression were assessed with validated questionnaires. Results Between group analyses: Participants with PPPD showed reduced activity in anterior cingulate cortex and increased activity in left angular gyrus in response to negative versus positive stimuli, which was not observed in recovered individuals. Within group analyses: Participants with PPPD had increased activity in visuospatial areas (parahippocampal gyrus, intraparietal sulcus) in negative versus positive and negative versus neutral contrasts, whereas recovered individuals had increased activity in anxiety regions (amygdala, orbitofrontal cortex). Conclusion Patients with PPPD may be more attuned to spatial elements than to the content of emotionally charged visual stimuli.